Effect of Free Fatty Acids on Myocardial Function and Oxygen Consumption in Intact Dogs - Mjøs, Ole D. (1971)
Myocardial function and oxygen consumption (MV̇O(2)) were studied during increased myocardial uptake of free fatty acids (FFA) induced by intravenous infusion of a fat emulsion (Intralipid) after heparinization in anesthetized and intact dogs. During raised myocardial uptake of FFA, MV̇O(2) increased in all experiments. On the average, MV̇O(2) rose from 8.6 to 10.7 ml/min·100 g, or 26% (P < 0.001). This was mainly due to elevated myocardial oxygen extraction, as myocardial blood flow was unchanged, or increased slightly. In the recovery period, MV̇O(2) returned to normal. Left ventricular pressure, the maximal rate of rise of left ventricular pressure (dP/dt), heart rate, and cardiac output remained unchanged during the raised myocardial uptake of FFA. These experiments show that increased myocardial uptake of FFA in intact hearts was associated with augmented MV̇O(2), despite unchanged mechanical activity.